Flower Retail in Kazakhstan: Business Plan - Abdigali, Alikhan; Baidauletov, Talgat (2010)
Executive summary Flower retail industry in Kazakhstan is estimated to be around USD $80-100 million. Current market environment allows for entrance of a new player, focused on highly lucrative part segment of the market. Our business will differentiate itself by offering exceptional level of service while retaining competitive market prices. This business plan describes a way to turn USD $204,000 into a business with a turnover above $ 7 million in four years by capturing premium 10% of the market. The investment is split between physical assets (USD $70K) and working capital requirements (USD $134K). The average margin accepted in this industry is over 100%, which allows this project to show very good profitability and reach pay-back period in two years. From marketing perspective, our value will come from adding our service to a relatively traditional product – flower. Professional and motivated staff, high quality flowers, décor and design of our shops will become a destination for affluent consumers who want to buy a present. Apart from traditional flowers our stores will sell unique chocolates and wines, along with Western style bouquets – which will serve as additional attraction to our customers.